PROSEDUR PEMBERIAN KREDIT PADA LEMBAGA PERKREDITAN DESA (LPD) DESA ADAT CENGKILUNG DENPASAR UTARA - Ni Luh Dia Ayu Ningtias; Ni Putu Trisna Windika Pratiwi; Rai Dwi Andayani W (UNHI Press, 2020)
LPD is a financial institution belonging to the Pakraman village that participates in the success of development, especially in the field of the village economy. The research with the title